Local Electoral Melawan Pemodal (Studi Tentang Strategi Akhmad Fatikhudin Dalam Pemilihan Kepala Desa Bulakwaru Kecamatan Tarub Kabupaten Tegal) - Zimamul Khaq, M.; Agustien, Resi (CV. Multi Kreasi Media, 2024)
This research examines Ahmad Fatikhudin's strategy in the 2019 Bulakwaru Village Head election, using a case study qualitative research method. The theories used are Peter Scroder's political strategy theory and Firmanzah's political marketing theory. From the research results, it was found that Ahmad Fatikhudin's strategy in the 2019 Village Head election used the Cooperate Strategy by applying the principle of cooperation within a small team led by Kyai Idris Salis to stem investors who from the start of the nomination wanted to control every Bulakwaru village head election, strengthening fellow Village Head candidates so that not easily persuaded to join with investors, working together with other Village Head candidates so that there are only 2 (two) Village Head candidates, so that the voting public is not confused by the many Village Head candidates, utilizing social capital as religious figures and community leaders who have previously occupied position of chairman of the District KPU. Tegal 2003-2008 and also a former member of the District DPRD. Tegal for the 2009-2014 period, legislative candidate for 2014-2019 and 2019-2024, actively campaigning for women from religious circles, offering a vision and mission as well as programs whose ideas come from the community, such as infrastructure and providing standby cars for all levels of society, and securing votes by village youths as the last bulwark in facing covert movements from investors so that people do not abstain from voting.